Naturally Occurring Variation in Trophoblast Invasion as a Source of Novel (Epigenetic) Biomarkers - Van DIjk, Marie; Visser, Allerdien; Posthuma, Janny; Poutsma, Ankie; Oudejans, Cees (Frontiers in Genetics, 2012)
During the first trimester of pregnancy fetal trophoblasts invade the maternal decidua, thereby remodelling the maternal spiral arteries. This process of trophoblast invasion is very similar to cancer cell invasion, with multiple signaling pathways shared between the two. Pregnancy-related diseases, e.g. pre-eclampsia, and cancer metastasis start with a decrease or increase in cellular invasion, respectively. Here, we investigate if first trimester placental explants can be used to identify epigenetic factors associated with changes in cellular invasion and their potential use as biomarkers. We show that the outgrowth potential of first trimester explants significantly correlates with promoter methylation of PRKCDBP and MMP2, two genes known to be differentially methylated in both placenta and cancer. The increase in methylation percentage coincides with an increase in invasion potential. Subsequently, as a non-invasive marker must be detectable in blood, plasma samples of pregnant and non-pregnant women were analyzed. The MMP2 promoter showed high methylation levels in non-pregnant plasma samples, which decreased in pregnant plasma. The decrease in methylated plasma DNA during pregnancy is most likely due to the fractional increase in unmethylated placental DNA. This suggests that the level of unmethylated DNA has the potential to be used as an invasion marker, where higher levels of unmethylated DNA indicate a lower invasion potential of trophoblasts. These proof of principle data provide evidence that human first trimester placental explants are an excellent ex vivo model system to identify (epigenetic) factors and thus potential biomarkers associated with changes in cellular invasion, e.g. to detect pregnancy-related diseases or cancer metastasis. To identify novel biomarkers the next step is to correlate naturally occurring variation in invasion potential to changes in (epigenetic) factors by genome-wide approaches such as massively parallel sequencing.